Aplikasi Algoritma Dijkstra dalam Penyelesaian Berbagai Masalah - Rosyid Ridlo Al Hakim; Muhammad Haikal Satria; Yanuar Zulardiansyah Arief; Agung Pangestu; Ariep Jaenul; Revita Desi Hertin; Dian Nugraha (EXPERT: Jurnal Manajemen Sistem Informasi dan Teknologi, 2021)
Dijkstra is a greedy algorithm that gives a choice of several available shortest routes and then provides a solution. The application of Dijkstra's Algorithm in everyday life is very diverse. This study collects research results regarding the application of Dijkstra's Algorithm to solve everyday problems such as the shortest path problem, this mini-review paper can explain the study of Dijkstra's Algorithm for various things, including solving bi-objective shortest routes, multi-objective routes, emergency evacuation, Dijkstra's graph, the connection between LBS features, best route distribution, and fuzzy solution.